ANALISIS PENGARUH INDIKATOR PENILAIAN TINGKAT KESEHATAN BANK BERBASIS RISIKO TERHADAP NILAI MARKET SHARE PADA BANK BUKU IV DI INDONESIA PERIODE 2009-2019 - Setiadi, Kelvin reinard; Suhartoko, Y. B. (Jurnal Manajemen, 2021)
In this study, the authors will analyze several financial ratios included in the bank health assessment indicators and are used to analyze the relationship between these ratios and the market share of banking in Indonesia. This research was conducted at BUKU IV bank using quarterly data from the 2009 to 2019 period obtained by the authors from the published reports of these banks. The author sees the importance and obligation for stakeholders, including regulators and the public to see market share information as a monitoring and awareness tool for the BUKU IV bank. That the BUKU IV bank has a major influence in realizing a healthy banking system, strong and efficient, as a company capable of influencing economic development in Indonesia (agent of development), has a major reputation risk to maintain stakeholder trust (agent of trust), and as a tool measure to see the satisfaction of banking services to the public (agent of services). The results of research using the Random Effect model showed that the Gross NPL variable, Net NPL had a negative and insignificant effect on the market share of BUKU IV in Indonesia. The variables of non-performing productive assets and non-productive assets with problems on total productive assets and non-productive assets have a significant negative effect on the market share of BUKU IV in Indonesia. The variables ROA, NIM, OEOI, KPMM, CKPN, problematic productive assets on total productive assets have a significant positive effect on the market share of BUKU IV in Indonesia. The CASA variable has a positive and insignificant effect on the market share of BUKU IV in Indonesia.